Seleção de peptídeos miméticos aos antígenos imunogênicos do vírus da anemia infecciosa equina e do vírus da leucose bovina, a partir de bibliotecas de phase display - Elizangela Maira dos Santos (2010)
Peptides displayed on phages were selected using phage display technology and immunoassays, for discovering antigenic mimetics of corresponding natural epitopes on immunogenic proteins of Equine Infectious Anemia virus and Bovine Leukemia virus. The use ofantigenic mimetics can improve the sensitivity and specificity of serological diagnosis for Equine Infectious Anemia (EIA) and Enzootic Bovine Leukosis (EBL), contributing directly to measures of diseases control. The selections allowed the choice of clones showing peptides sequences with potential applications in diagnosis. The sequence displayed by phage E12 has potential for use as antigen in diagnostic tests for EIA, and other nine sequences were selected for use asantigens in tests for EBL. Synthetic peptides produced from selected sequences can be considered potential candidates for use as antigens in serological tests for diagnosis of EIA and EBL.